Change of Selected Parameters of Steel Surface after Plasma Nitriding - Dobrocky, David; Pokorny, Zdenek; Studeny, Zbynek; Dostal, Petr (Manufacturing Technology Journal, 2019)
This article deals with the evaluation of the change of selected 2D structure parameters of the grinded surfaces before and after application of plasma nitridation. Changes in parameters were analyzed on 30CrMoV9 steel samples which were ground to Ra ≈ 0.03 and then plasma nitrided in a standard nitriding atmosphere. An absolute method was used to evaluate the surfaces. Measurements were performed on a profilometer CLI 1000. The parameters comprehensively describing the surface structure were subjected by analyzes, namely the height, length, shape parameters and parameters of the material ratio. After plasma nitriding, almost all selected surface structure parameters have been increased. Higher values of the monitored parameters have an influence on the increase of friction and wear and negatively affect the running-up properties of nitrided components.
Keywords: Grinded surface; Structure; Roughness; Plasma nitridation; Microgeometry